Effect Program Educational Based on According to Raigloth Expansion Theory in Teaching Post-Modern Arts for Students of the Institute of Fine Arts: Pengaruh Program Pendidikan Berdasarkan Teori Ekspansi Raigloth dalam Pengajaran Seni Rupa Post-Modern untuk Mahasiswa Institut Seni Rupa - Mohammed, Hussein Jabbar (Indonesian Journal of Education Methods Development, 2024)
General Background: The evolving landscape of postmodern art necessitates innovative educational approaches to equip students with the skills and knowledge required to navigate this complex field. Specific Background: This research investigates the impact of an educational program grounded in Reigeluth's expansive theory on the teaching of postmodern art at the Institute of Fine Arts in Baghdad. Prior studies have highlighted the need for effective instructional designs that engage students and enhance their cognitive achievements. Knowledge Gap: Despite the proliferation of educational theories, there remains limited empirical evidence on the effectiveness of expansive instructional design in the context of postmodern arts education. Aims: This study aims to assess the effectiveness of an expansive educational program on students' cognitive achievement in postmodern art compared to traditional teaching methods. Results: Utilizing an experimental design with two equivalent groups, the findings reveal statistically significant differences (p < 0.05) in post-test scores favoring the experimental group that engaged with the educational program based on Reigeluth's theory. Novelty: This research contributes to the literature by demonstrating that an expansive instructional approach can significantly enhance students' understanding and appreciation of postmodern art. Implications: The results underscore the necessity for art education curricula to incorporate innovative instructional designs that foster deeper cognitive engagement and mastery of complex artistic concepts. By bridging the gap between theory and practice, this study offers valuable insights for educators seeking to improve instructional effectiveness in the rapidly evolving domain of postmodern art. Highlights: Impact of expansive design on cognitive achievement in postmodern art. Controlled study shows significant differences in student performance outcomes. Innovative teaching methods enhance student engagement and understanding. Keywords: postmodern art, educational program, Reigeluth's theory, cognitive achievement, instructional design